2008
DOI: 10.1186/1471-244x-8-46
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Thai version of the PHQ-9

Abstract: Background: Most depression screening tools in Thailand are lengthy. The long process makes them impractical for routine use in primary care. This study aims to examine the reliability and validity of a Thai version Patient Health Questionnaire (PHQ-9) as a screening tool for major depression in primary care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
268
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 315 publications
(320 citation statements)
references
References 26 publications
7
268
2
1
Order By: Relevance
“…Consistent with previous studies in adults [23][24][25][26][27][28][29]39 and adolescents, 33 the current study also found that the Chinese version of the PHQ-9 has a high reliability, as evidenced by the internal consistency (Cronbach' s a = 0.84). The test-retest reliability of the PHQ-9 was fair but slightly lower than in previous reports on adults [27][28][29]40 and adolescents.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with previous studies in adults [23][24][25][26][27][28][29]39 and adolescents, 33 the current study also found that the Chinese version of the PHQ-9 has a high reliability, as evidenced by the internal consistency (Cronbach' s a = 0.84). The test-retest reliability of the PHQ-9 was fair but slightly lower than in previous reports on adults [27][28][29]40 and adolescents.…”
Section: Discussionsupporting
confidence: 79%
“…21 In addition, it can monitor changes in depression symptoms after intervention. 22 The PHQ-9 is widely used in adult patients in primary care, [23][24][25][26] older adults with chronic illnesses, 27 and university students. 28 In Taiwan, the PHQ-9 and its 2 subscales (2 items, PHQ-2 and 1 item, PHQ-1) have been validated among adults in primary care and demonstrated good psychometric properties.…”
mentioning
confidence: 99%
“…If the score was ≄8, it indicated a hazardous drinker (8)(9)(10)(11)(12)(13)(14)(15) or harmful user (16)(17)(18)(19) or alcohol dependence (≄20).…”
Section: Instrumentsmentioning
confidence: 99%
“…Convergent validities were also found, from .56 (Lotrakul, Sumrithe, & Saipanish, 2008) to .74 http://dx.doi.org/10.15405/epsbs.2016.07.02.39 eISSN: 2357-1330 responsibility of the Organizing Committee of the conference 413 (Changsu et al, 2008). A meta-analysis of Gilbody, Richards, Brealey and Hewitt (2007) found a high sensitivity (.80) and specificity (.92).…”
mentioning
confidence: 96%
“…Moreover it has been adapted to different languages and cultures, such as Brazilian (OsĂłrio et al, 2009), Thai (Lotrakul et al, 2008), Greek (Karekla, Pilipenko, & Feldman, 2012), Saudi Arabian (Becker, Zaid, & Faris, 2002), Taiwanese (Liu et al, 2011), Chinese (Yeung et al, 2008), Korean (Changsu et al, 2008), Spanish (Diez-Quevedo et al, 2001), Mexican (Donlan & Lee, 2010), French (Carballeira et al, 2007), Nigerian (Adewuya et al, 2006), Turkish (GĂŒleç, GĂŒleç, Simsek, Turhan, & SĂŒnbĂŒl, 2012) and Japanese (Yu et al, 2012). The PHQ-9 has been reported to have a single factor in several previous studies Dum, Pickren, Sobell, & Sobell, 2008;Graves & Bombardier, 2008;Hansson, Chotai, Nordstöm, & Bodlund, 2009;Yu et al, 2012), including a study involving more than 5000 primary care patients (Huang, Chung, Kroenke, Delucchi, & Spitzer, 2006).…”
mentioning
confidence: 99%